XRTSDIC: model transformation from PIM to PSM - Ramesh, G (International Journal of Engineering and Technology, 2018)
Computer Aided Software Engineering (CASE) has been growing faster in software industry. As part of it Model Driven Engineering (MDE) has been around for focusing on models and transforming them from one model to other model. The tool named Extensible Real Time Software Design Inconsistency Checker (XRTSDIC) proposed by us in previous paper supports UML modelling, design inconsistency checking and model transformation from UML to ERD to SQL. In this paper it is extended further to facilitate model transformation from PIM (UML class diagram) to PSM (source code). We proposed an algorithm and defined model transformation and consistency rules. The extended framework has provision for class relationship analysis and support for choosing different object oriented languages like C#, C++ and Java. While transforming the model, we used the concept of dialects. Dialect is the class with transformation functionality which has ability to adapt to syntax and semantics of chosen language. Different dialects are made available for different languages. Thus the proposed system is capable of transforming models and the prototype application we built and extended demonstrates the proof of concept. The empirical results revealed that the model transformation is consistent and accurate.